2023
DOI: 10.3389/fpubh.2023.1097675
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic risk factors among children who are affected by overweight, obesity and severe obesity

Abstract: BackgroundThe increasing severity of obesity is expected to lead to more serious health effects. However, there is limited information on the prevalence and clinical characteristics of cardiometabolic risk factors in severely children affected by obesity in Malaysia. This baseline study aimed to investigate the prevalence of these factors and their association with obesity status among young children.MethodsIn this study, a cross-sectional design was employed using the baseline data obtained from the My Body I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…We analysed the dietary data and metabolic indicators of 623 participants enrolled in SEACO-CH20, comprising 285 children (aged 7-12) and 389 adolescents (aged [13][14][15][16][17][18]. Most respondents were Malay, with almost equal proportions of males and females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analysed the dietary data and metabolic indicators of 623 participants enrolled in SEACO-CH20, comprising 285 children (aged 7-12) and 389 adolescents (aged [13][14][15][16][17][18]. Most respondents were Malay, with almost equal proportions of males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent Malaysian community-based study reported a lower MetS prevalence of 4.8% in children 14 , Wan Mahmud et al 15 reported a high MetS prevalence of 56% among children with obesity and adolescents among those referred to obesity clinics in tertiary care. The study suggests children with MetS were 14 times more likely to be severely obese.…”
mentioning
confidence: 94%
“…A recent analysis conducted on pediatric patients has demonstrated that HDL levels were inversely correlated with patients’ BMI, while a direct correlation could be found with other lipid indices [ 31 ]. These observations are consistent with the general characteristics of patients with CPP, who typically tend to have higher BMI compared to children with normal pubertal development [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%